Lake Ladoga The Coastal History of the Greatest Lake in Europe - Lähteenmäki, Maria; Land, Isaac (Studia Fennica Historica, 2023)
Aimed at researchers, students and all interested in history, this multidisciplinary study offers a spectacular view of the history of Europe's largest lake. Adopting the lens of coastal history, this edited volume presents the development of the vast Great Lake's catchment area over a long-time span, from archaeological traces to Viking routes and from fishery huts to luxury villas of the power elite. It reflects on people's sensory-historical relationships with aquatic nature, and considers the benefits and harms of power plants and factories to human communities and the environment. The focus of the study is on the central and northern parts of the shores of Lake Ladoga, which belonged to Finnish rule between 1812 and 1944. The multidisciplinary approach permits an unusually wide range of questions. What has the Great Lake meant to local residents in cultural and emotional terms? How should we conceptualize the extensive and diverse networks of activities that surrounded the lake? What kind of Ladoga beaches did the Finns have to cede to the Soviet Union at the end of the war in 1944? How have Finns reminisced about their lost homelands? How have the Russians transformed the profile of the region, and what is the state of Ladoga's waters today? The volume is the first overall presentation of Lake Ladoga, which today is entirely part of Russia, aimed at an international readership. The rich source material of cross-border research consists of both diverse archival material and chronicles, folklore, reminiscence, and modern satellite images. The history of Lake Ladoga helps readers to understand better the economic, political, and socio-cultural characteristics of the cross-border areas, and the dynamics of the vulnerable border regions.